Dementia awareness, beliefs and barriers among family caregivers in Pakistan. (April 2021) - Balouch, Sara; Zaidi, Asghar; Farina, Nicolas; Willis, Rosalind
Objectives: Dementia research and services in Pakistan are limited. The following was explored in experiences of family caregivers of people with dementia in Pakistan: (a) to determine whether culture and religion play a role in caregiving; (b) to draw insights on how family caregivers cope, what barriers they face and what help they would be willing to accept and (c) to determine how these findings could be used to raise awareness and influence public policies in improving the lives of families living with dementia. Methods: The experiences of family caregivers of people with dementia in Pakistan were explored via semi-structured interviews (10 in Lahore; 10 in Karachi). This was part of a larger qualitative study conducted about dementia in Pakistan. Caregivers interviewed were aged 35–80 (14 female). Most caregivers in the study were educated and affluent. Interviews were conducted in Urdu, translated into English and thematically analysed. Results: Five themes emerged: knowledge and awareness; stigma; importance of religion and duty to care; use of day care centres and home-help; and barriers. A lack of dementia awareness exists in Pakistan. The religious duty to care for family influenced caregiving decisions. Day care centres and home-help were accessed and viewed positively. The caregivers also wanted extracurricular activities for people with dementia, support groups for caregivers and better training for healthcare staff. Novel findings included that caregivers felt that dementia should not be stigmatised, and awareness should be raised in Pakistan via TV, radio and social media, but not inside mosques. Discussion: Additional research is necessary to determine if positive views of day care centres and home-help exist more widely. Attitudes and experiences regarding stigma may be different for caregivers of people with more advanced dementia. We recommend raising dementia awareness, allocating more funds to dementia services and an emphasis on home-based care.